Design of Micro- and Nanoparticles: Self-Assembly and Application - Stoikov, Ivan; Padnya, Pavel (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Objects of nanotechnology such as micro- and nanoparticles are very interesting due to their unique properties. This reprint will be useful to scientists of diverse backgrounds, i.e., material science, organic and inorganic chemistry, biochemistry, and biology.